2018
DOI: 10.1111/vde.12682
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of the use of lokivetmab in the management of allergic pruritus in a referral population of 135 dogs in the western USA

Abstract: Lokivetmab at labelled dosages was a fast, safe and efficacious therapy for the control of pruritus in dogs with allergic dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 11 publications
7
78
2
1
Order By: Relevance
“…Moreover, the broad definition used herein is similar to those used in other clinical studies. 12,13 It is considered unlikely that the selected broad cAD (bsAD) definition used herein markedly influenced the calculated disease prevalence in WHWT by the time the dogs had reached early adulthood. An overall disease prevalence of 52% in WHWT may be perceived as very high; however, this breed has been shown for a long time to be predisposed to this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the broad definition used herein is similar to those used in other clinical studies. 12,13 It is considered unlikely that the selected broad cAD (bsAD) definition used herein markedly influenced the calculated disease prevalence in WHWT by the time the dogs had reached early adulthood. An overall disease prevalence of 52% in WHWT may be perceived as very high; however, this breed has been shown for a long time to be predisposed to this disease.…”
Section: Discussionmentioning
confidence: 99%
“…The definition is in keeping with clinical trials. 12,13 The broader definition was used for all analyses.…”
Section: Definition Of Ad and Its Severitymentioning
confidence: 99%
“…It has been shown to be as effective as ciclosporin for the control of pruritus and inflammation in CAD over a period of three months with a more rapid onset of action (often within 24 hours) (Moyaert and others 2017). In one study 77 per cent of dogs treated had a greater than or equal to 50 per cent reduction in owner-assessed levels of pruritus and clinical improvement was noted within 24 hours in 56 per cent of dogs treated (Souza and others 2018). In the same study it was noted that response to oclacitinib is to some degree a good predictor of whether the case will response to lokivetmab, although many cases that had a poor or no response to once daily oclacitinib still responded to lokivetmab.…”
Section: Lokivetmab – a New Biological Therapy For Cadmentioning
confidence: 98%
“…Oclacitinib has a short half-life in the dog and as a result of this clinical experience has shown that many cases are well controlled with twice daily therapy but there is often some recurrence of pruritus on reduction to once daily treatment, although most cases are still obviously improved compared to pretreatment (Souza and others 2018). For this reason, and because oclacitinib is only licensed for once daily treatment when used long term, we will often initiate treatment on a once daily basis, as this avoids the inevitable client concern when there is some recurrence of pruritus when treatment is reduced from twice to once daily.…”
Section: Oclacitinib – a New Pharmacotherapy For Cadmentioning
confidence: 99%
See 1 more Smart Citation